2017
DOI: 10.1097/mlr.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Valuation and Modeling of EQ-5D-5L Health States Using a Hybrid Approach

Abstract: This paper shows the feasibility of using a hybrid approach to estimate a value set for EQ-5D-5L valuation data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
169
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(170 citation statements)
references
References 26 publications
0
169
0
1
Order By: Relevance
“…Here, we applied the new EQ-5D-5L value sets from eight countries [16][17][18][19][20][21][22][23]: England, the Netherlands, Spain, Canada, Uruguay, China, Japan, and Korea. For ease of exposition, the English value set would be emphasised, though results for other countries' value sets were discussed.…”
Section: Measures Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we applied the new EQ-5D-5L value sets from eight countries [16][17][18][19][20][21][22][23]: England, the Netherlands, Spain, Canada, Uruguay, China, Japan, and Korea. For ease of exposition, the English value set would be emphasised, though results for other countries' value sets were discussed.…”
Section: Measures Of Variablesmentioning
confidence: 99%
“…A key limitation of this previous study is that it was based on an interim value set, which was a 'cross walk' between the earlier three-level 2 EQ-5D (EQ-5D-3L) and the EQ-5D-5L descriptive system [15]. Most recently, several country-specific EQ-5D-5L value sets have been published, including four Western countries (England, the Netherlands, Spain, Canada), three Asian countries (China, Japan, Korea) and one South American (Uruguay) [16][17][18][19][20][21][22][23]. Hence, the existing mapping algorithm for D-39 is becoming obsolete following the publication of these new EQ-5D-5L value sets.…”
Section: Introductionmentioning
confidence: 99%
“…The use of version 1.0 of the protocol to conduct EQ-VT-based valuation studies showed several issues related to the quality of the resulting data [10,11]. The most obvious of these was a relatively high rate of logically inconsistent responses, a formal definition of which can be found in the Methods section.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this paper is to find out whether the smoking status of the general Spanish population is associated with systematic variations in HRQoL as measured by the EQ-5D-5L valuation questionnaire instrument [7,8] once biological and clinical conditions are controlled for.…”
Section: Introductionmentioning
confidence: 99%
“…individuals representing a population of 38.6 million. The ENS2011-12 is the first ENS that contains information on the EQ-5D-5L self-report questionnaire [7,8]. (25% males and 23% females).…”
Section: Introductionmentioning
confidence: 99%